Marginal cord insertion in the first trimester is associated with furcate cord insertion - Zhuan Yu; Yu-Zhou Liu; Zheng Zhang; Bao-Ding Chen; Xin Zhang (BMC, 2024)
Abstract Objectives To evaluate the potential connections between marginal cord insertion during the first trimester and furcate cord insertion later in pregnancy. Methods This is a prospective study of screening data on the cord insertion site in 3178 singleton pregnancies. The cord insertion site was examined in two stages. The first stage was screening for the cord insertion site between 10-13 weeks of gestation, the purpose is to determine the category of umbilical cord insertion. The second stage, performed at 22-28 weeks of gestation, was to follow up on the relationship between the cord insertion site and the placenta and to identify any changes in the category of umbilical cord insertion. This was performed to diagnose or exclude furcate cord insertion by identifying whether the umbilical cord trunk separated or branched before it reached the placenta. Factors influencing progression to furcate cord insertion and perinatal complications were assessed. Results Fourteen cases (0.44%) with progression to furcate cord insertion, all of which showed marginal cord insertion on ultrasound in the first trimester (p < 0.001). without progression to furcate cord insertion, there were no changes in the category of umbilical cord insertion in 3050 cases (96.40%) compared to the early pregnancy. 114 cases (3.60%) with changes in the category of umbilical cord insertion that was not consistent with furcate cord insertion. A total of 14 cases progressed to furcate cord insertion, all showed the cord insertion site were in close proximity, and 11 (78.57%) cases showed a low insertion site (p < 0.001). Regarding the choice of mode of delivery, elective caesarean delivery was done in 8/14 (57.14%). The incidences of spontaneous vaginal delivery were 5/14 (35.71%) (p < 0.001). One (7.14%) case of progression to furcate cord insertion due to haematoma at the root of the umbilical cord ended with an emergency caesarean section. In terms of perinatal complications, marginal cord insertion that progressed to furcate cord insertion had higher incidences of SGA infants, abnormal placental morphology, retention of the placenta, and cord-related adverse pregnancy outcomes than not progressed to furcate cord insertion (p < 0.05). Conclusions Marginal cord insertion in the first trimester has the potential to progress to furcate cord insertion. We suggest that ultrasound-diagnosed marginal cord insertion in the first trimester should be watched carefully in the second trimester, which is clinically useful to accurately determine the category of cord insertion and to improve the rate of prenatal diagnosis of furcate cord insertion.